Fresh Fish Consumption Behaviour in Padang City, Indonesia - Junaidi Junaidi; Desi Ilona; Zaitul Zaitul (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2020)
The fresh fish consumption behaviour has been attracting the previous researchers. Unfortunately, few studies based on Indonesia were held by the researchers. Due to the lack of the previous study, the purposes of the study are to investigate the influence of attitudes, control of perceived behaviour, and subjective norm on intention to consume fish, and to examine the relationship of the fish consumption intention with consumption behaviour. The study applies plan behaviour theory to understand the raised phenomena in this paper. The number of respondents participated in this study is fifty-five. SEM-PLS is used to analysis data supported by assessment of measurement and structural model as the smart-pls procedure. The results indicate that there is a positive effect of attitude toward behaviour on intention to consume fish. Besides, fish consumption intention also has a significant association with consume behaviour. However, the effect of the norm and control of perceived behaviour on fish consumption intention is not significant. This finding confirms the theory of plan behaviour. Practically, this finding shows implicitly that to increase the fish behaviour consumption, the intention to consume fish and attitude toward fish consume behaviour should be increased.